Hupa Language Literature and Culture. Third Edition - California State Univ.-Humboldt, Arcata. Center for Community Development; Parsons, Tom; California State Univ.-Humboldt, Arcata. Center for Community Development ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
One in a series of materials developed to revive the Hupa language and renew knowledge of Hupa culture, this lexicon includes vocabulary, phrases, and stories in Hupa and English. The major portion of the document is an English-Hupa lexicon of basic vocabulary listed alphabetically by the English words. In addition to the Hupa and English terms, notes in English offer further explanation such as the information that angelica root is used for medicine in ceremonial dances and that the literal translation of the Hupa word for blue jay would be "up jumps limb to limb." Following the basic lexicon are seven lists of terms specific to Hupa culture in the categories of geography (ceremonial sites, villages, town and place names), number system, money system, calendar, baskets and tools, flora, and wildlife (birds, marine life, land animals). Following the vocabulary lists are six pages of frequently used expressions and phrases. The documents is completed by five stories in Hupa with English translations: "Medicine for Making Infants Grow Fast,""Toad Story,""Gooseberry Place Brush Dance,""Medicine for Making Baskets," and "Origin of Fire." (JHZ)
ERIC Note: Some pages may not reproduce well due to marginal legibility. Printing courtesy of the Bureau of Indian Affairs, Hoopa Area Office. For related documents, see RC 016 267-275. Best copy available.
Students.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: American Indian Culture; American Indian Education; American Indian Languages; Basic Vocabulary; Bilingual Instructional Materials; Cultural Education; Definitions; Elementary Secondary Education; Language Maintenance; Legends; Mythology; Native Language Instruction; Phonemic Alphabets; Reading Materials; Cultural Literacy -- Hupa; Hupa (Tribe) -- UNIFON Alphabet; Reference Materials, Vocabularies/Classifications.; Guides, Classroom -- Learner; Multilingual/Bilingual Materials